Still Here - Kristine Gustavsen Madsø; Inger Hilde Nordhus (Age, Culture, Humanities)
Following the completion of a clinical research project assessing music therapy for home-dwelling people with dementia and their significant other, we developed an interactive photo exhibition, “Still here,” that was launched on World Alzheimer´s Day, September 21st, 2021, in the city center of Bergen. We aimed to communicate to the local citizens how music may facilitate experiences of positive identity and relational mutuality for people with dementia and their significant others. Stereotypes about loss and decline still characterize the mainstream discourse of dementia. Myths, misconceptions, and stigma are associated with dementia and have a significant impact on the people who live with the condition. We aimed to portray a different narrative of dementia to the public, a narrative of resilience and creative capacity—and, in so doing, to knowingly recuperate and communicate the idea of psychological resilience in contradistinction to the neoliberal constructions of this concept. We intended to reflect a perspective closer to how individuals describe or experience living with dementia. This paper tells the story of how the exhibition was developed to disseminate the findings of our research project, elaborating on the challenges current narratives on dementia present in our field and how the photographs became narrators of another story of dementia.